The Watchman an sms-based system administrator - Diamante, Dominic P.; Romero, Joan Rachel P.; Isla, Jhoanna T. (2006)
Desktop PC owners deal with the problem of controlling the use of their PC regardless of geographical location. The Watchman aims to provide a system administrator with means to securely manage and monitor his remote desktop PC using SMS technology. The Watchman provides the following features: view running procedures, view memory usage (with CPU state information), kill running processes, process monitoring, reboot or shut down the target PC, user help, logging of administrator requests and host replies. The administrator sends a text message containing the password and the command. The message is sent through the GSM modem connected to the administrator's desktop PC. The message is further sent to Kannel and according to the configuration file (smskannel.conf), a parser (written in C) accepts the message and performs the specific command. If a reply is needed, a reply message is sent back to the administrator. The Watchman has been tested by the authors and has performed the necessary operations.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Computer systems -- Management; Computer security; Telecommunication -- Message processing; Watchman